A mild and convenient one-pot photochemical synthesis of chroman-4-one derivatives. the photo-Fries rearrangement of (hetero)aryl 3-methyl-2-butenoate esters under basic catalysis - Samaniego Lopez, Cecilia (2010)
The biphasic base catalysis-mediated photo-Fries rearrangement reaction of aryl 3-methy-2-butenoate esters in room temperature cyclohexane - 10% KOH system was investigated. This mild photochemical reaction leads to the formation of chroman-4-one derivatives in good to high yield and in short reaction times (30-120 min) in a one-pot photochemical reaction. Also, the photochemical reaction, as a convenient, versatile, and general method, applies efficiently to polycyclic and heterocyclic 3-methy-2-butenaote esters.